Baseline and Post-exercise High-Sensitivity C-Reactive Protein Levels in Endurance Cyclists: The Indonesian North Coast and Tour de Borobudur 2017 Study - Mahalul Azam; Susanti Lestari; Sri Ratna Rahayu; Arulita Ika Fibriana; Budhi Setianto; Nyoman Suci Widyastiti; Suhartono Suhartono; Hardhono Susanto; Martha Irene Kartasurya; Udin Bahrudin; Thijs Eijsvogels (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Inflammation plays an important role in the atherosclerotic process. High-sensitivity C-reactive-protein (hs-CRP) is commonly used as inflammatory biomarker. It is well known that regular physical activity lowers hs-CRP levels, while prolonged exercise induces hs-CRP elevations. However, the relationship of training and exercise characteristics with hs-CRP levels remains not well elucidated. We evaluated baseline and post-exercise hs-CRP levels and its association with training and exercise characteristics.METHODS: Eighty-eight male endurance cyclists were involved. Demographic data, health condition and training characteristics were collected. Baseline and postexercise blood-samples were collected to determine hsCRP concentrations. A hs-CRP cut-off point of 3 mg/L was used. Blood-cell count and biochemical parameters were measured at baseline. Heart rate (HR) was measured during exercise.RESULTS: Cyclists performed 7.3 hours (interquartilerange (IQR) = 5.4-7.5) of endurance exercise at intensity of 81.8 % (IQR = 74.9-85.8). Cyclists with baseline hsCRP ≥ 3 mg/L reported higher body mass, body mass index (BMI), waist-circumference and total-cholesterol. An increase in hs-CRP was following endurance exercise. Cyclists with any elevation of hs-CRP reported a higher BMI, HR during exercise and exercise intensity. Binary logistic regression analysis showed BMI (OR = 1.24, 95% CI = 1.04-1.48) and cycling distance (OR = 0.22, 95% CI = 0.06-0.76) were associated with post-exercise hs-CRP elevations.CONCLUSION: Body mass, BMI, waist-circumference, total- and HDL-cholesterol are associated with baseline hsCRP, whereas BMI and cycling distance were associated with hs-CRP elevations. These findings suggest that anthropometry parameters and lipid levels attributed to baseline hs-CRP, while anthropometry parameters and cycling intensity attributed to post-exercise hs-CRP elevations.KEYWORDS: C-reactive-protein, exercise, endurancecycling, inflammation, acute-phase-response